My RESPITE: Malaysian resources for spiritual care training - Nasution Raduan, Nor Jannah; Katiman, Diana; Md Rosli, Ahmad Nabil; Zulkifli, Emy Shahida; Hashim, Nurul Azreen (Hub for Innovative Teaching and Learning (HITeL), UiTM Cawangan Perak, 2020)
Spiritual care in clinical practice is a relatively new domain in medicine, especially in Malaysia. The importance and relevance of spiritual care to patients' health and wellbeing should not be underestimated. Standardized training on basic spiritual care is required in order to deliver it effectively. Based on their cultural and spiritual backgrounds, some healthcare workers may hold pre-conceived ideas on what spiritual care is, which may not suit the patients. During these unprecedented times of COVID-19 pandemic, the classical learning method through face-to-face interaction is limited in order to reduce the risk of transmission. For this purpose, a webpage is developed to furnish students with a virtual counterpart of experiential learning for students. My RESPITE: Malaysian Resources For Spiritual Care is a team of healthcare providers who have become the pioneer in spiritual care among Malaysian healthcare providers. The team consists of clinicians; hospital chaplains and nurses, who have received 0.5 units of training from Clinical Pastoral Education of Central California. My RESPITE is a novel innovation developed with an objective of exposing healthcare workers, students and volunteers to the spiritual care of patients. Training via video series was developed in a webpage to provide access to spiritual care training and knowledge. Several short videos are pre-recorded and posted on the webpage, which serves as important resources for students. An expert on clinical, spiritual care was consulted prior to developing the content of the videos. The topics range from basic spiritual care concepts, skills and assessment tools, to other topics related to spirituality and mental health. My RESPITE provides accessibility for an engaging training in spiritual care. It will create awareness to healthcare workers, students and volunteers on the importance of spiritual care in patients from all types of backgrounds. All stakeholders will be more aware and open towards ones own spiritual needs to reach one’s ultimate meaning in life.